Balancing flexibility and security in Europe? The impact of unemployment on young peoples' subjective well-being. (September 2020) - Russell, Helen; Leschke, Janine; Smith, Mark
We examine the relationship between 'flexicurity' systems, unemployment and well-being outcomes for young people in Europe. A key tenet of the flexicurity approach is that greater flexibility of labour supply supports transitions into employment, trading longer-term employment stability for short-term job instability. However, there is a risk that young people experience greater job insecurity, both objective and subjective, with less stable contracts and more frequent unemployment spells. Our research draws on data from the European Social Survey and uses multi-level models to explore whether and how flexibility-security arrangements moderate the effect of past and present unemployment on the well-being of young people. We distinguish between flexibility-security institutions that foster improved job prospects and those that provide financial security.